2018
DOI: 10.1007/s10741-018-9719-7
|View full text |Cite|
|
Sign up to set email alerts
|

Flow-mediated dilation and heart failure: a review with implications to physical rehabilitation

Abstract: Endothelial dysfunction plays as an important role on mismatch responses that occur during exercise in patients with congestive heart failure (CHF). However, cardiac rehabilitation, a core component of management of CHF patients, can improve endothelial function, contributing to reduce the morbidity and mortality of these patients. The primary aims of this review were to describe the importance of flow-mediated dilatation (FMD) as a non-invasive validation tool to assess endothelial dysfunction and to highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 84 publications
0
22
0
1
Order By: Relevance
“…Considering HFpEF as a multisystem disease with endothelial dysfunction representing the key mechanism of such systemic maladaptation, targeting endothelial function has been recently proposed as a new appealing approach for future HFpEF therapies. 8,13 It has been reported that exercise is able to increase blood flow and shear stress, thus positively impacting NO bioavailability and endothelial function. 58 Moreover, exercise may induce changes to the adrenergic system in addition to its ability to recruit endothelial progenitor cells from the bone marrow.…”
Section: N Of Studies N Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering HFpEF as a multisystem disease with endothelial dysfunction representing the key mechanism of such systemic maladaptation, targeting endothelial function has been recently proposed as a new appealing approach for future HFpEF therapies. 8,13 It has been reported that exercise is able to increase blood flow and shear stress, thus positively impacting NO bioavailability and endothelial function. 58 Moreover, exercise may induce changes to the adrenergic system in addition to its ability to recruit endothelial progenitor cells from the bone marrow.…”
Section: N Of Studies N Of Patientsmentioning
confidence: 99%
“…10 In detail, a systemic pro-inflammatory state with increased oxidative stress and subsequent endothelial dysfunction have been proposed as key mechanisms in the development of cardiac remodelling and left ventricular (LV) diastolic dysfunction in HFpEF patients. 11,12 Thus, due to its systemic nature and reversibility in early stages, endothelial dysfunction may represent an attractive therapeutic target in this clinical setting, 13,14 with a potential emerging role for exercise training and cardiac rehabilitation in HFpEF patients. 15,16 Among a number of available techniques, brachial artery flow-mediated dilation (FMD) and nitrate-mediated dilation (NMD) are recognized as accurate and noninvasive methods for estimating endothelial function by means of ultrasound (US) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…the body's local nitric oxide (NO) bioavailability in the endothelium. Thus, impairment in FMD in pre-clinical subjects is related to a number of risk factors [3], and a reduction in FMD is predictive for a cardiovascular disease [8]. However, clear additional prognostic value for endothelial function has not been found [9].…”
Section: Introductionmentioning
confidence: 99%
“…During periods of increased perfusion, where the v of blood increases, endothelial cells release nitric oxide to stimulate arterial smooth muscle vasorelaxation, a process known as flow mediated dilatation (FMD). Importantly, FMD is a prognostic indicator of future cardiovascular disease (Areas et al 2019) and is quantified clinically during ischaemia-reperfusion testing. The magnitude of FMD (i.e.…”
Section: Introductionmentioning
confidence: 99%